Inclusion of Students with Intellectual Dizabilities in the Mass: Personalyzed Intervention Plan - Denisa Szilagyi; Ion Albulescu (Babes-Bolyai University, 2023)
For students with intelectual disabilities, inclusion, seen as a process, is the most effective way to combat discriminatory attitudes towards this category of students, a proces that will help them become independent adults in the future. Also, inclusion among students with intellectual disability in a class in ordinary education is the best proof that education is accessible but also equal for each student, regardless of the particularities of its psycho-physical development. In order for these students to have access to a quality education, the class teacher must design a personalized intervention plan for each subject, but also some strategies to improve the inclusion process. Our paper contains a personalized intervention plan (P.I.P.) in the disciplines of Communication in Romanian and Mathematics and Environmental Exploration for a student with moderate intellectual disability in the first grade who is studying in mass education. Our personalized intervention plan also meets learning needs, pursues and promotes methods and strategies to improve the school inclusion process for the student with moderate intellectual disability.